Systematic Literature Review : Penerapan Design Thinking Dalam Pembelajaran Siswa Tingkat SMA/Sederajat - Angga Dinata; Anggun Sagita Sagita; Anneke De Resta; Annisa Maulidah Nurzain Nurzain; Annisa Zakiya (FKIP - Universitas Pahlawan Tuanku Tambusai, 2025)
21st century education demands innovative learning approaches to develop students' critical thinking, creativity, and problem-solving skills. One relevant approach is design thinking, which is oriented towards creative and collaborative problem-solving with systematic stages such as empathy, define, ideate, prototype, and test. This article aims to evaluate the application of design thinking in learning for high school/equivalent students through a Systematic Literature Review (SLR) method. Data was collected from 41 articles spanning 2015-2025, with 5 articles selected as primary sources. The analysis results show that design thinking has a positive impact on students' critical thinking abilities, creativity, and innovation. However, challenges such as lack of teacher understanding and limited resources are major obstacles in its implementation. This study provides in-depth insights into the benefits, challenges, and implementation strategies of design thinking to create more adaptive and relevant learning at the secondary education level.